A new multimodulus blind equalization algorithm - Abrar, Shafayat (2004)
A new algorithm is presented for the blind equalization of complex signals. This algorithm can be considered as a variant of the well-known reduced constellation algorithm (RCA). The proposed algorithm is obtained by removing the discontinuity found in the RCA cost function. The steady-state performance of the proposed algorithm is demonstrated by simulations. In addition, closed form expressions are obtained for the dispersion constants and the minimum of the cost functions. The phase-recovery and intersymbol interference optimization properties, exhibited by the proposed algorithm, are also discussed.